"Let the Fear Go and Trust the Process" - Experiencing Grounded Theory Over a Lifetime: Odis E. Simmons in Conversation With Astrid Gynnild - Simmons, Odis (Forum, qualitative social research, 2024)
Odis SIMMONS was among the first students who learned grounded theory method (GTM) directly from the co-founders GLASER and STRAUSS. Except for GLASER himself, SIMMONS is probably the grounded theorist who has taught the method to most students globally. In this interview SIMMONS provides key insights into learning, doing, teaching, and applying classic grounded theory (GT) as a general research method. With his double background as a therapist and a teacher in higher education, SIMMONS elaborates on fears that students might have during the research process and how they are overcome. He explains the ideas behind his own approaches to grounded action and grounded therapy, which for a long time resided in the GTM background but are gradually getting more widespread. In the interview, he also brings new knowledge on the diverging perspectives of GLASER and STRAUSS which, according to him, existed from the beginning. He argues, in an including manner, why classic GTM and constructivist GTM should be considered two different methods and urges educators to openly discuss the differences.